Odpowiedź :
[tex]A=(-2,-1) \ \ \rightarrow \ \ x_{A} = -2, \ \ y_{b} =-1\\\\B = (6,3) \ \ \rightarrow \ \ x_{B} = 6, \ \ y_{B} = 3\\\\S = (\frac{x_{A}+x_{B}}{2}, \frac{y_{A}+y_{B}}{2} )\\\\S = (\frac{-2+6}{2}, \frac{-1+3}{2})\\\\\boxed{S = (2, 1)} \ - wspolrzedne \ srodka \ odcinka \ AB[/tex]
[tex]|AB| = \sqrt{(x_{B}-x_{A})^{2}+(y_{B}-y_{A})^{2}}\\\\|AB| = \sqrt{(6-(-2))^{2}+(3-(-1))^{2}} = \sqrt{8^{2}+4^{2}} = \sqrt{64+16} = \sqrt{80} =\\\\= \sqrt{16\cdot5} = 4\sqrt{5}[/tex]
[tex]\boxed{|AB| = 4\sqrt{5}} \ - \ dlugosc \ odcinka \ AB[/tex]